Analysis of Iranian Muslim Gay Profile Uploads in @Thequeermuslimproject Instagram Account - Nara Garini Ayuningrum (Muwazah, 2021)
Instagram as a new media offering free and global seems to be a means of "escaping" from the real repression received by Saif, Danyal and Alireza as homosexual Muslims, from the social pressures and religious discourse that dominate Iran. This paper is about the analysis of representations by the three, who claim to be homosexual Muslims who grew up in Iran. The representations of the three were analyzed through their own self-photos and profile captions on the instagram account page of @thequeermuslimproject, an online community for Muslim queers, using the multimodal critical discourse analysis (CDA) method put forward by Gunther Kress and Theo Van Leeuwen, which is an analysis method used to analyze text in the form of images and writings. Research becomes interesting when the representations shown are not identical or different from each other despite growing up in the influence or dominance of the same discourse. Researchers summarize it into 3 major discourses found in the representations shown by the three, namely (a) the practice of coming out, (b) the dominance of heteronormatic discourse, and (c) the politics of visibility.